Video Self-Modelling as an Interactive Learning Tool in enhancing Student’s Engagement in Physical Activity - Calubayan, Lovely D.; Ofrin, Darwin O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study sought to investigate the students’ perception on the video self-modelling as an interactive learning tool in enhancing their engagement in physical activity in terms of its acceptability, usability, functionality, frequency and relevance, their level of students’ engagement in physical Activity as in their authentic engagement, strategic compliance, intellectual engagement, social engagement and behavioral engagement. Furthermore, this also examine the significant relationship between Video self-modelling As an Interactive Learning Tool and Student Engagement in Physical Activity. The researcher utilized the constructed survey questionnaire to the selected Grade 11 and Grade 12 Senior High School Students of San Isidro National High School, General Luna, Quezon, to gather data needed in the study. The participants were selected through stratifies sampling technique. Furthermore, the mean, the standard deviation and Pearson r were used as statistical tool. It was revealed that the students accept the video-self modeling as it is easy to use, rich in content, and interesting interactive tool in PE subject. Further, through video-self modeling, the students develop positive behavior, improved existing skills, performed well in physical activities, was motivated, understand the lesson, and boost the confidence and self-esteem, Moreover, the video-self modelling as an interactive tool has significant relevance to the students engagement.